Perancangan dan Pembuatan Sistem Infomasi Peminjaman dan Pengembalian Rekam Medis di Puskesmas Arjasa Kabupaten Situbondo - Nuril Firdausiah; Andri Permana Wicaksono; Novita Nuraini; Bakhtiyar Hadi Prakoso (Indonesian Journal Publisher, 2025)
Medical record service activities at the Arjasa Community Health Center in Situbondo Regency still often experience missfiles. A missfile is a medical record file that is misplaced or not found on the medical record storage shelf in the filling room. This missfile occurs because there is no device that controls the entry and exit of medical records, meaning that incoming and outgoing medical records are not recorded in either the medical record tracer or expedition book. resulting in delays in returning medical records to both inpatient and outpatient units. The time limit for borrowing medical records in the outpatient unit is 1x24 hours and 2x24 hours for inpatient care. To minimize delays in returning medical record data which can result in missfiles, this project aims to design and create an information system for borrowing and returning medical records at the Arjasa Community Health Center, Situbondo Regency. This type of research is Research and Development research using the Waterfall method. Data collection was carried out by interviews, documentation and observation. This research produces a website-based information system for borrowing and returning medical records with the advantage of reminders on WhatsApp users. Program flowcharts, data flow diagrams, and entity relationship diagrams are used in designing this information system, and the black box testing method is used for testing.